Appraisal Of Oil Properties - Earl Oliver (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
THE term oil property, in this discussion, includes any type of easement or grant under which petroleum might be produced; it ranges from the mere right to drill on undeveloped wildcat acreage up to a fully developed oil property. The values of an oil property, as thus defined, vary widely according to the use for which it is intended, whether it is from the viewpoint of the speculator, the fraudulent stock promoter, the refiner and pipe-line owner, or the oil producer. The market value of a property is usually a combination of some two or more of these influences, and occasionally a combination of all of them, but we prefer to treat each viewpoint as distinct from the others, allowing the reader to make his own combination in such proportions as his inclination and property seem to require. This paper will treat the subject from the viewpoint of the oil producer. However, the other influences have such bearing on the cost of property to the producer and on the price he might obtain by its sale as to warrant brief discussion of them. Speculation, particularly lease speculation, is a parasitic growth on the oil industry, healthy enough, but of no economic value. The class of property usually dealt in for this purpose is the undeveloped lease. Its speculative value may have some relation to its probable productive value, but most frequently this value is the product of temporary excitement due to local development. The lease speculator, seeking out the trend of development or securing early information regarding a proposed test or a new discovery, immediately secures leases whose market value will be increased when the existence of such development becomes more widely known. His profits are purely unearned increment. Not proposing to spend money in exploration, he can afford to compete in purchase with the operator, who, in addition to bonus paid, must spend large sums in testing out his own acreage and that of the nearby speculator as well. It has a tendency to compel unduly high bonuses.